2014
DOI: 10.3389/fenrg.2014.00041
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among the Energy, Emergy, and Money Flows of the United States from 1900 to 2011

Abstract: Energy Systems Language models of the resource base for the U.S. economy and of economic exchange were used, respectively, (1) to show how energy consumption and emergy use contribute to real and nominal gross domestic product (GDP) and (2) to propose a model of coupled flows that explains high correlations of these inputs with measures of market-based economic activity. We examined a third power law model of growth supported by excess resources and found evidence that it has governed U.S. economic growth sinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…These metrics of energy quality in one way or another account for "energy plus technology" rather than simply gross primary energy consumption. This quality factor is often one based upon relative prices of resources (e.g., the price per MJ is higher for oil than coal) [46], thermodynamic characterizations such as fuel exergy, technology conversion efficiency, and "useful work" delivered [5,6,10,18], or embodied energy concepts such as emergy [47,48]. The work of Ayres is particularly enlightening to show that energy, expressed as useful work (e.g., light, mechanical motion, heat, etc.…”
Section: Summary Of Econometric Perspectivesmentioning
confidence: 99%
“…These metrics of energy quality in one way or another account for "energy plus technology" rather than simply gross primary energy consumption. This quality factor is often one based upon relative prices of resources (e.g., the price per MJ is higher for oil than coal) [46], thermodynamic characterizations such as fuel exergy, technology conversion efficiency, and "useful work" delivered [5,6,10,18], or embodied energy concepts such as emergy [47,48]. The work of Ayres is particularly enlightening to show that energy, expressed as useful work (e.g., light, mechanical motion, heat, etc.…”
Section: Summary Of Econometric Perspectivesmentioning
confidence: 99%
“…The primary results of this study are reported in Appendix B as a table of values showing the emergy required to educate individuals to achieve varying levels of education from preschool to the doctoral degree with 2 years postdoctoral experience. The values of the emergy per individual are based on the emergy inputs to the U.S. given in [34,35]. Other results of this study are reported in the text, figures and tables presented below.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the higher emdollar one area had, the less developed it was [33]. As the near-linear correlation between real GDP and total emergy inputs [34], the UEV of the Chinese Yuan (¥) in 2017 was 3.31 × 10 11 seJ/¥ under 12.0 × 10 24 seJ/year baseline which was calculated based on the UEV (7.27 × 10 11 seJ/¥ with 9.26 × 10 24 seJ/year baseline) calculated by Yang (2010) in 2005 and the GDP deflator of 2005 to 2017 (2.84) [33,35]. In this study, the global emergy baseline was 12.00 × 10 24 seJ/year.…”
Section: Emergy Analysismentioning
confidence: 94%